2011
DOI: 10.1097/bsd.0b013e3182064632
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Hinge Position on the Effectiveness of Expansive Open-door Laminoplasty for Cervical Spondylotic Myelopathy

Abstract: Our results indicate that proper inward shift of the hinge can ensure effectiveness of surgical decompression, avoid an excessive backward shift of the spinal cord, reduce the incidence of C5 palsy, and alleviate the severity of axial symptoms. In addition, an inward shift should be cautious and contraindicated in patients with fluorosis cervical stenosis, ossification of posterior longitudinal ligament, and ossification of ligament flavum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…73,74 The hinge position determines how open the door is and an inward shift of the hinge restricts excessive backward shift and overstretching of the nerve roots. 71 Although no patients in the narrow-group experienced C-5 palsy and 3 cases were seen in the wide group, this difference did not reach statistical significance. However, there was a lower incidence of this complication following laminoplasty with concurrent foraminotomy, suggesting that another potential cause of C-5 palsy is existing C-4/C-5 foraminal stenosis.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…73,74 The hinge position determines how open the door is and an inward shift of the hinge restricts excessive backward shift and overstretching of the nerve roots. 71 Although no patients in the narrow-group experienced C-5 palsy and 3 cases were seen in the wide group, this difference did not reach statistical significance. However, there was a lower incidence of this complication following laminoplasty with concurrent foraminotomy, suggesting that another potential cause of C-5 palsy is existing C-4/C-5 foraminal stenosis.…”
Section: Discussionmentioning
confidence: 76%
“…57 Similarly, hinge position (wide group: hinge located at the inner margin of the lateral mass; narrow group: hinge at the lamina margin) was not associated with the development of C-5 palsy (p = 0.17). 71 In a comparative study between open-door and doubledoor laminoplasty, C-5 palsy rates tended to be higher following open-door laminoplasty (p < 0.05). 34 Selective expansive open-door laminoplasty (EOLP) was designed to reduce damage to cervical posterior elements and prevent common long-term problems of laminoplasty, such as axial symptoms, malalignment, and decreased range of motion.…”
Section: Laminoplasty Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Xia et al [19] reported that in open-door laminoplasty, patients with a relative lateral through on the hinge side .were more susceptible to C5 palsy. Zhang et al [14] considered that the lamina open angle in laminoplasty should be maintained between 15°∼30°, or otherwise the risk of postoperative C5 palsy may increase.Radcliff et al [17] found a wider laminectomy at C5 and an increased diameter of the spinal canal were associated with an increased risk of C5 palsy.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] Despite presumed advantages, open-door laminoplasty is not uniformly accepted compared with laminectomy and fusion due to several drawbacks, including reclosure problems, hinge fracture, and potential injuries to the nerve roots or the spinal cord by bone grafts at the open side. [6][7][8][9] Controversy over laminoplasty still exists. Some recent studies reported good outcomes with plate-only open-door laminoplasty in patients with cervical spinal canal stenosis in which mini-plates were used to reconstruct the spinal canal.…”
mentioning
confidence: 99%